2015
DOI: 10.1080/09507116.2015.1036531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat input on the mechanical properties of welded joints in high-strength steels

Abstract: Experiments were carried out to determine the properties of the welded joints in 8 mm thick high-strength steels produced by quenching and tempering and thermomechanical rolling with accelerated cooling (tensile strength 821-835 MPa). The dependence of the strength, elongation, hardness, impact energy and crack opening displacement on the heat input in the range 1.0 -0.7 kJ mm 21 was determined. The results show that the dependence of the strength of the welded joints decreases and that of the elongation incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…7(b) that the higher the Δt 8/5 in the weld metal, the lower the microhardness measure in the HAZ and WM. Therefore, probably the main factor for the microhardness reduction in the HAZ and WM was the heat input increase, as the results presented by [17], [20], [22], and [23].…”
Section: Microhardness and Cooling Rates (δT 8/5 )mentioning
confidence: 82%
See 1 more Smart Citation
“…7(b) that the higher the Δt 8/5 in the weld metal, the lower the microhardness measure in the HAZ and WM. Therefore, probably the main factor for the microhardness reduction in the HAZ and WM was the heat input increase, as the results presented by [17], [20], [22], and [23].…”
Section: Microhardness and Cooling Rates (δT 8/5 )mentioning
confidence: 82%
“…The cooling time between 800 °C and 500 °C is often used in welding. The reason is that the cooling rate of the welded joint is very important to determine its microstructure and mechanical properties [2], [18], [19], especially in HAZ [20]. The local microstructure and the properties of any point along the weld bead are determined by the thermal cycle undergone at the point in question, with the peak temperature decreasing as distance from the weld bead center line increases [18], [21].…”
Section: Microhardness and Cooling Rates (δT 8/5 )mentioning
confidence: 99%
“…Effect of the welds have not been taken into account in temperature distribution analysis. Based on the mechanical studies [18][19] welding process has multiple effect on the connection properties. However, Franssen [16] proved that in context of heat distribution a model without the weld offers an acceptable prediction.…”
Section: Experimental Observationmentioning
confidence: 99%
“…However, they seemed to not consider the effect of the microstructural gradient and the impact of different microhardness in the various HAZ regions. As a result, researchers studied the tensile properties of undermatch welds of QT HSS RQT701 for different heat inputs [23]. It was observed that an increase in the heat input values produces a coarsening of the microstructure of the weld metal (WM) and the HAZ.…”
Section: Introductionmentioning
confidence: 99%